THE ROLE OF THE PROPHET IN EDUCATING CHILDREN AND ITS IMPLEMENTATION IN PREVENTING GADGET ADDICTION IN CHILDREN - Maulana Hasan Hasibuan; Alwi Padly Harahap; Aurora Hanifah (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
Currently, technological advances are rapidly developing worldwide, including in Indonesia. One technology that is currently attracting a lot of attention from the public, including children, is gadgets. However, the use of these gadgets sometimes causes people to become addicted to using them if they are not controlled. This research aims to determine the role of the Prophet in educating children and its implementation in preventing gadget addiction in children. This research uses qualitative research with descriptive-analytic data analysis techniques. The results of this research show that Prophet Muhammad has an important role in educating children, contributing to efforts to prevent gadget addiction in children. In addition, parents also play an important role in preventing gadget addiction in children, especially by being good role models as the Prophet was a role model for his people. It is very important for parents to build good communication with their children by applying teachings of the Prophet Muhammad in interacting with children. Likewise, discipline in educating children provides valuable lessons for parents in guiding their children with clear, consistent, and loving rules. Finally, parents can help children choose friends who have positive habits or engage in other creative activities that do not involve excessive use of gadgets. By emulating the Prophet's way of educating children, parents can be more effective in preventing gadget addiction in children, forming good character, and instilling strong religious values from an early age.